Economic development and climate change. Which is the cause and which the effect?. (November 2020) - Copiello, Sergio; Grillenzoni, Carlo
Abstract: Energy efficiency has established as a trending topic in scholarly research in the last four decades. Lately, the purpose of that research strand has broadened so to tackle the increase of greenhouse gas emissions and the issues related to climate change. Human beings and their mass production and consumption activities are thought to be a primary source of climate-altering emissions. However, that assumption has been seldom tested. Here we aim to provide a methodological and empirical framework to check for the causal nexus that allegedly ties together demographic growth, economic development, and climate change. The analysis is based on the historically reconstructed series of several variables that span over the last centuries. Besides, it is based on the class of ARIMAX-ARCH models. The results show evidence for bidirectional causation between human growth and climate change. In particular, we find that solar irradiance and gross domestic product are significant predictors of temperature anomalies. Furthermore, temperature anomalies and solar irradiance are found to exert a positive feedback effect on the growth rate of gross domestic product. As regards the causality measures, despite the strength of the univariate component, the contribution of the exogenous factors is strongly significant in all the estimated models. The analysis we carry out suggests framing climate change within a set of long-run trends.